Avoiding the dangers of pesticides - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
'Pesticides: Composition, Use and Hazards' by Wilma Arendse, Koen den Braber, Inge van Halder, Inge Hoogerbrugge, Marleen Kramer, Harold van der Valk, Agrodok 29 1989, 56pp plus appendices. Available from: Agromisa - PO Box 41 - 6700 AA Wageningen THE